SURVEY OF FOOD SAFETY MEASURED IN THE CANTEEN OF AUTOMOBILE SECTOR COMPANIES OF AURANGABAD MIDC AFTER COVID 19 (International Journal of Food and Nutritional Sciences, 2022)
India is a country where industrial development is a wave to strengthen the country’s economy. But in this development employee welfare is not been looked at very well. Employee welfare includes canteen facility .and these canteens Food safety is always an issue when it comes to large canteen management. Most of the time these canteens were operated in the industrial sectors providing food to 150-2000 or more people at a time. They work in two shifts serving breakfast, lunch, high tea, snacks, and dinner. As per the company, policy food is provided to work as a part of its welfare and costs extra to the company. These facilities are very basic and mostly outsourced by a private contractor or on very few occasion company management run itself. Workers of these units always talk about food quality, hygiene, cleanliness, and the attitude of food handlers and found that they are not very satisfied after many efforts of the company. This affects the culture of the organization and the attitude of workers working there for more than 5-10 -20 years or more. It also affects absenteeism, and health-related issues of workers related, to foodborne diseases in long run within the service span of employees. A close survey of the store management, cooking procedure, service of food, workplace standard, statutory requirement, and personal hygiene of food handlers was collected and a suggestion was given to fill the gap for improving the food safety of some industrial canteens. . Close survey of the store management, cooking procedure, service of food, workplace standard, statutory requirement and personal hygiene of food handlers was collected and the suggestion was given to fill the gap for the improvement in the food safety of some industrial canteens.